Taarikh wa Tathwiir Madaaris al Nushuuh fi al Andalusiyah wa Mishr: Diraasah li Ta'siiriha 'alaa 'ilmi al Lughah al 'Arabiyyah - Hidayati, Hidayati; Asrina, Asrina (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
The study of Arabic began with the many problems and errors in the way Arabs spoke. The purpose of this study, known as nahwu, was to protect the Arabic language in the Qur'an from these errors. Starting from the first nahwu school in Basrah, and later, new schools emerged in Kufa, Baghdad, Andalusia, and Egypt. as well as the role of local scholars in developing and critiquing classical nahwu. Each of these schools has its own characteristics and history, which then resulted in different rules and teaching methods. Andalusia as the center of the spread of Islamic civilization in the western region has an important role in the spread of knowledge. This study examines the history of the Andalusian and Egyptian schools of thought, as well as the figures who helped shape them. This study uses library research methods to examine related materials and data collection techniques through document review, namely collecting, reviewing, and analyzing scientific manuscripts related to the science of nahwu in Andalusia and Egypt.